Longitudinal and cross-sectional structural magnetic resonance imaging correlates of AV-1451 uptake - Das, Sandhitsu R.; Xie, Long; Wisse, Laura E.M.; Ittyerah, Ranjit; Tustison, Nicholas J.; Dickerson, Bradford C.; Yushkevich, Paul A.; Wolk, David A. (Neurobiology of aging, 2018)
We examined the relationship between in vivo estimates of tau deposition as measured by 18F-AV-1451 tau positron emission tomography imaging and cross-sectional cortical thickness, as well as rates of antecedent cortical thinning measured from magnetic resonance imaging in individuals with and without evidence of cerebral amyloid in 63 participants from the Alzheimer's Disease Neuroimaging Initiative study, including 32 cognitively normal individuals (mean age 74 years), 27 patients with mild cognitive impairment (mean age 76.8 years), and 4 patients diagnosed with Alzheimer's disease (mean age 80 years). We hypothesized that structural measures would correlate with 18F-AV-1451 in a spatially local manner and that this correlation would be stronger for longitudinal compared to cross-sectional measures of cortical thickness and in those with cerebral amyloid versus those without. Cross-sectional and longitudinal estimates of voxelwise atrophy were made from whole brain maps of cortical thickness and rates of thickness change. In amyloid-β–positive individuals, the correlation of voxelwise atrophy across the whole brain with a summary measure of medial temporal lobe (MTL) 18F-AV-1451 uptake demonstrated strong local correlations in the MTL with longitudinal atrophy that was weaker in cross-sectional analysis. Similar effects were seen in correlations between 31 bilateral cortical regions of interest. In addition, several nonlocal correlations between atrophy and 18F-AV-1451 uptake were observed, including association between MTL atrophy and 18F-AV-1451 uptake in parietal lobe regions of interest such as the precuneus. Amyloid-β–negative individuals only showed weaker correlations in data uncorrected for multiple comparisons. While these data replicate previous reports of associations between 18F-AV-1451 uptake and cross-sectional structural measures, the current results demonstrate a strong relationship with longitudinal measures of atrophy. These data support the notion that in vivo measures of tau pathology are tightly linked to the rate of neurodegenerative change.